INVESTIGATION OF THE EFEECT OF TBLT-BASED DIGITAL STORYBOOK ON STUDENTS’ SPEAKING SKILL IN SMP LABORATORIUM UNDIKSHA SINGARAJA - Mahadewi, Pande Made Ayu; Paramartha, A.A. Gede Yudha; Wahyuni, Luh Gede Eka (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
This study aims to investigate the significant effect of TBLT-based digital storybook on eighth grade students’ speaking skill in SMP Laboratorium Undiksha Singaraja. This study was quantitative research which used quasi-experimental design. This research assigned two classes; experimental which consisted of 19 students and control class which consisted of 18 students. The two classes were given different treatment; TBLT-based digital storybook was treated in Experimental class and Teacher’ usual method was treated in Control Class. Speaking test was used to obtain speaking score. T-test formula was used to analyze the data. The result showed that there was a significant effect of TBLT-based digital storybook on students’ speaking skill. It was proven by the Sig. (2-tailed) value was 0.000. Thus, the significance value of the tests was less than 0.05. This shows that there is significant effect on students’ speaking skill who taught using TBLT-based digital storybook compared with student taught by using teacher usual method. Additionally, the effect size value measured using Cohen’s d was 1.291. This large effect means that the implementation of TBLT-based digital storybook can provide a very real influence in the improvement of students' speaking skills compared to the teacher’s usual method.